Editorial Note - Munga, Cosmas (Multidisciplinary Journal of Technical University of Mombasa, 2023)
Editorial Note We would like to thank all our authors and co-authors who contributed to original scientific articles for the successful release of this 2nd Issue of MJTUM Volume 2. This issue has a total of 6 original scientific research articles from a diverse array of fields ranging from hospitality and tourism, communication studies, public health, and building and civil engineering. The content of all the articles is from dedicated research works from the authors and co-authors. MJTUM is hereby providing a platform to share the contents of these research works in contributing to knowledge dissemination to the scientific community and to all students in their quest to advance knowledge in their respective fields covered in this second issue. MJTUM will continue to give a platform for sharing of scientific articles of high quality to all our readers. It is my sincere hope that you will enjoy reading the wide coverage of articles covered in this issue as we prepare you for the release of MJTUM Volume 3 Issue 1 as soon as possible. Dr. Cosmas Nzaka Munga (PhD) Chief Editor, MJTUM